Analysis of buccal mucosa as a prognostic tool in children with arrhythmogenic cardiomyopathy. (March 2022) - Bueno-Beti, Carlos; Field, Ella; Tsatsopoulou, Adalena; Perry, Gregory; Sheppard, Mary N.; Behr, Elijah R.; Saffitz, Jeffrey E.; Kaski, Juan Pablo; Asimaki, Angeliki
Abstract: Background: The diagnosis of arrhythmogenic cardiomyopathy (ACM) is challenging especially in children at risk of adverse events. Analysis of cardiac myocyte junctional protein distribution may have diagnostic and prognostic implications, but its utility is limited by the need for a myocardial sample. We previously reported that buccal mucosa cells show junctional protein redistribution similar to that seen in cardiac myocytes of adult patients with ACM. Objectives: We aimed to determine when junctional protein distribution abnormalities first occur in children with ACM variants and whether they correlate with progression of clinically apparent disease. Methods: We analyzed buccal mucosa samples of children and adolescents with a family history of ACM ( n  = 13) and age-matched controls (n = 13). Samples were immunostained for plakoglobin, desmoplakin, plakophilin-1 and connexin43 and analyzed by confocal microscopy. All participants were swabbed at least twice with an average interval of 12–18 months between samplings. Results: Junctional protein re-localization in buccal mucosa cells did not correlate with the presence of ACM-causing variants but instead occurred with clinical onset of disease. No changes in protein distribution were seen unless and until there was clinical evidence of disease. In addition, progressive shifts in the distribution of key proteins correlated with worsening of the disease phenotype. Finally, we observed restoration of junctional signal for Cx43 in patient with a favorable response to anti-arrhythmic therapy. Conclusions: Due to ethical concerns about obtaining heart biopsies in children with no apparent disease, it has not been possible to analyze molecular changes in cardiac myocytes with the onset/progression of clinical disease. Using buccal smears as a surrogate for the myocardium may facilitate future studies of mechanisms and pathophysiological consequences of junctional protein redistribution in ACM. Buccal cells may also be a safe and inexpensive tool for risk stratification and potentially monitoring response to treatment in children bearing ACM variants.